2004
DOI: 10.1091/mbc.e03-09-0675
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling Is Involved in Dynein-dependent Microtubule Organization

Abstract: The microtubule cytoskeleton supports cellular morphogenesis and polar growth, but the underlying mechanisms are not understood. In a screen for morphology mutants defective in microtubule organization in the fungus Ustilago maydis, we identified eca1 that encodes a sarcoplasmic/endoplasmic calcium ATPase. Eca1 resides in the endoplasmic reticulum and restores growth of a yeast mutant defective in calcium homeostasis. Deletion of eca1 resulted in elevated cytosolic calcium levels and a severe growth and morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 53 publications
9
41
0
Order By: Relevance
“…Thus, it is possible that ketamine suppresses F-actin and microtubular cytoskeletons by means other than through inhibition of ␣-and ␤-actins or microtubulin expression. A previous study showed that levels of calcium can trigger cytoskeletal remodeling and regulate cell motility (Adamíková et al, 2004;Fache et al, 2005). The present results revealed that ketamine alleviated the bradykinin-induced enhancement of intracellular calcium.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, it is possible that ketamine suppresses F-actin and microtubular cytoskeletons by means other than through inhibition of ␣-and ␤-actins or microtubulin expression. A previous study showed that levels of calcium can trigger cytoskeletal remodeling and regulate cell motility (Adamíková et al, 2004;Fache et al, 2005). The present results revealed that ketamine alleviated the bradykinin-induced enhancement of intracellular calcium.…”
Section: Discussionsupporting
confidence: 66%
“…Cytoskeletal remodeling requires calcium and energy (Molitoris et al, 1996;Fache et al, 2005). Previous studies showed that calcium mobilization can trigger cytoskeletal remodeling and regulate cell activities (Adamíková et al, 2004;Fache et al, 2005). The ischemia-reperfusion process leads to mitochondrial dysfunction and ATP depletion, and such decreases in cellular ATP levels induce cytoskeleton disruption, which can damage endothelial cells (Nishimura et al, 1998).…”
mentioning
confidence: 99%
“…S. cerevisiae calmodulin has diverse essential functions as revealed by a study of intragenic complementation of conditional mutants, and the defects observed in three of the complementation groups (cmd1A, cmd1B, and cmd1D) indicate that calmodulin may function at multiple steps of the pathway controlling morphogenesis in yeast (39). The regulation of actin organization is a common theme revealed by these previous studies in yeast; however, recent reports have also identified a role for calcium signaling in microtubule dynamics in other fungi (1,15).…”
Section: Discussionmentioning
confidence: 93%
“…In C. neoformans, this gene regulates resistance to various stresses and growth at 37°C and functions in parallel with and upstream of the calcineurin pathway. The closest homolog is the ECA1 gene of the related basidiomycete plant-pathogenic fungus U. maydis, in which the ECA1 gene was identified by analysis of a temperature-sensitive mutant (1). The growth phenotypes of the U. maydis and C. neoformans eca1 mutants are very similar.…”
Section: Discussionmentioning
confidence: 99%
“…In the parasite Leishmania mexicana amazonesis, a SERCA-type Ca 2ϩ pump (Lmaa1) is involved in virulence (59). In the basidiomycete plant pathogen Ustilago maydis, ECA1 encodes a SERCA required for growth at high temperature and hyphal development (1).…”
mentioning
confidence: 99%